Intermediate accounting - Keiso, Donald E.; Weygandt, Jerry J.; Warfield, Terry D. (Hoboken : John Wiley Sons, 2008)
Business
Keywords: Intermediate accounting; Accounting; Financial accounting; Income statement; Balace sheet; Cash flow; Valuation; Intengible assets; Current liabilities; Stokholders; Investment; Income tax